Dapoxetine Treatment Leads to Attenuation of Chronic Unpredictable Stress Induced Behavioral Deficits in Rats Model of Depression - Muhammad Farhan,; Hira Rafi ,; Hamna Rafiq, (Journal of Pharmacy and Nutrition Sciences, 2015)
Stressful conditions possess a complex relationship with brain and body’s reaction to stress and beginning of depression. The hypofunctioning of Serotonin (5-Hydroxytryptamine; 5-HT) is known to be established in unpredictable chronic mild stress exposure. UCMS is broadly taken as the most promising and favorable model to study depression in various animals, imitating many human depressive symptoms. With the class of selective serotonin [5-hydroxytryptamine (5-HT)] reuptake inhibitors (SSRIs) is now considered as the most prescribed antidepressant that can reverse petrochemical and behavioral effects of stresses. The aim of the present study was to investigate whether repeated administration of dapoxetine at dose 1.0 mg/kg could reversed the behavioral deficits induced by UCMS in rat model of depression. Rats exposed to UCMS revealed a significant reduction in food intake as well as growth rate. Locomotive activity in home cage and anxiolytic behavior in light/dark activity box were greater in animals of unstressed group as compared to animals of stressed group. The mechanism involved in the inhibition of serotonin reuptake at pre-synaptic receptors by repeated dapoxetine administration is discussed. The knowledge accumulated may facilitate an innovative approach for extending the therapeutic use of dapoxetine and the interaction between stress and behavioral functions.